Peran dan Tanggung Jawab Kepala Sekolah dalam Manajemen Berbasis Sekolah di SD Negeri 1 Beratan - Putu Diah Puspayanti; Anak Agung Istri Diah Adnyaswari; Ni Made Mira Darmayanti; I Made Agastiya; Basilius Redan Werang; Dewa Ayu Novi Kusumawardani (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2025)
This study aims to analyze the role and responsibilities of the principal in the implementation of School-Based Management (SBM). Basic education plays a crucial role in shaping the character and quality of human resources, necessitating effective and efficient school management. In this context, the principal is the primary actor in optimizing the implementation of SBM through strategic and participatory leadership. This study was conducted at SD Negeri 1 Beratan, with the principal as the subject. The study employed a descriptive qualitative approach with semi-structured interviews with the principal as the primary data source. The results indicate that the principal plays a role as a leader, manager, facilitator, supervisor, and motivator, all of which are carried out in an integrated manner. As a leader, the principal is responsible for planning and implementing school programs, including budget management, resource management, improving educational quality, accountability, and establishing relationships with the community. Therefore, the success of SBM implementation is strongly influenced by the optimization of the principal’s role and responsibilities in managing all aspects of education effectively and sustainably.